SOX9 and HMGB3 co‐operatively transactivate NANOG and promote prostate cancer progression. Issue 5 (21st December 2022) - Xu, Yunyi; Xu, Miao; Li, Xinglan; Weng, Xin; Su, Zhengzheng; Zhang, Mengni; Tan, Junya; Zeng, Hao; Li, Xun; Nie, Ling; Gong, Jing; Chen, Ni; et al.
Abstract: Background: The homeodomain‐containing transcription factor NANOG is overexpressed in prostate adenocarcinoma (PCa) and predicts poor prognosis. The SOX family transcription factor SOX9, as well as the transcription co‐activator HMGB3 of the HMGB family, are also overexpressed and may play pivotal roles in PCa. However, it is unknown whether SOX9 and HMGB3 interact with each other, or if they regulate NANOG gene transcription. Methods: We identified potential SOX9 responsive elements in NANOG promoter, and investigated if SOX9 regulated NANOG transcription in co‐operation with HMGB3 by experimental analysis of potential SOX9 binding sites in NANOG promoter, reporter gene transcription assays with or without interference or artificial overexpression of SOX9 and/or HMGB3, and protein‐binding assays of SOX9‐HMGB3 interaction. Clinicopathologic and prognostic significance of SOX9‐HMGB3 overexpression in PCa was analyzed. Results: SOX9 activated NANOG gene transcription by preferentially binding to a highly conserved consensus cis‐regulatory element (−573 to −568) in NANOG promoter, and promoted the expression of NANOG downstream oncogenic genes. Importantly, HMGB3 functioned as a partner of SOX9 to co‐operatively enhance transactivation of NANOG by interacting with SOX9, predominantly via the HMG Box A domain of HMGB3. Overexpression of SOX9 and/or HMGB3 enhanced PCa cell survival and cell migration and were significantly associated with PCa progression. Notably, Cox proportional regression analysis showed that co‐overexpression of both SOX9 and HMGB3 was an independent unfavorable prognosticator for both CRPC‐free survival (relative risk [RR] = 3.779，95% confidence interval [CI]: 1.159–12.322, p = 0.028) and overall survival (RR = 3.615，95% CI: 1.101–11.876, p = 0.034). Conclusions: These findings showed a novel SOX9/HMGB3/NANOG regulatory mechanism, deregulation of which played important roles in PCa progression.